Toward a theory of conflict in the franchise system - Spinelli, Steve; Birley, Sue (Journal of Business Venturing, 1996)
A focused review of the literature is presented in support of a definition of franchising as an interorganizational form examined from the entrepreneurship perspective. Then, microeconomic and relational exchange theories provide guidance within a transaction-cost economics theoretical framework to begin the formulation of a theory of conflict in franchising. The analysis provided in this article involves business format franchising. We submit that the essential core and uniqueness of business format franchising is the relationship between the franchisee and franchisor. Our definition of franchising requires a review of individual franchisee and franchisor organizational structures. Therefore, our theoretical analysis begins with a fundamental look at the economic structural differences of the average franchisor and franchisee firms, using microeconomic theory. This review points to the potential for conflict in profit-maximizing behavior between franchisee and franchisor. The likelihood is that the differences in behavior will manifest in pricing, promotion, and new store development. Next, because most business format franchising is contractually based and long-term, we investigate the theoretical support for establishing and continuing a relationship with fundamental areas of conflict. Relational exchange theory is used for this analysis. Transaction-cost economics provides a perspective on the governance of the interorganizational form and guides us in the investigation of the ongoing state of the relationship. A key to transaction-cost analysis is shared assets in the relationship and the degree of transferability of those assets. Therefore, building and maintaining the franchise trademark becomes the theoretical focus for governance of the relationship. We propose that franchisor-provided services is the principal method of franchisor contract fulfillment and is the framework for informal governance of the relationship. The importance and adequacy of the transactions between the franchisee and franchisor affect the perceived value of the trademark and are key to continuing the franchise relationship. Finally, the conflict literature is briefly reviewed to provide a context for the discussion of conflict in franchising and to illustrate that conflict can have a positive or negative effect on the relationship.